Fracture experience among participants from the FROCAT study: what thresholding is appropriate using the FRAX tool?. (January 2016) - Azagra, R.; Zwart, M.; Aguyé, A.; Martín-Sánchez, J.C.; Casado, E.; Díaz-Herrera, M.A.; Moriña, D.; Cooper, C.; Díez-Pérez, A.; Dennison, E.M.
Highlights: Previously, a Spanish FRAX risk thresholds of risk had been proposed from FRIDEX cohort. We display the suggested algorithm in the FROCAT, a population based cohort. The main fracture risk categories (low, intermediate, high) show concordance. The frequencies of fragility fractures over 10-year period are similar in FRIDEX and FROCAT cohorts. Abstract: Objective: To perform an external validation of FRAX algorithm thresholds for reporting level of risk of fracture in Spanish women (low <5%; intermediate ≥5% and <7.5%; high ≥7.5%) taken from a prospective cohort "FRIDEX". Methods: A retrospective study of 1090 women aged ≥40 and ≤90 years old obtained from the general population (FROCAT cohort). FRAX was calculated with data registered in 2002. All fractures were validated in 2012. Sensitivity analysis was performed. Results: When analyzing the cohort (884) excluding current or past anti osteoporotic medication (AOM), using our nominated thresholds, among the 621 (70.2%) women at low risk of fracture, 5.2% [CI95%: 3.4–7.6] sustained a fragility fracture; among the 99 at intermediate risk, 12.1% [6.4–20.2]; and among the 164 defined as high risk, 15.9% [10.6–24.2]. Sensitivity analysis against model risk stratification FRIDEX of FRAX Spain shows no significant difference. By including 206 women with AOM, the sensitivity analysis shows no difference in the group of intermediate and high risk and minimal differences in the low risk group. Conclusions: Our findings support and validate the use of FRIDEX thresholds of FRAX when discussing the risk of fracture and the initiation of therapy with patients.